Impact of Legal Regulation and Credit Access on MSME Competitiveness with NIB Ownership Mediation - Nindya Kartika Kusmayati; Iwang Suwangsih; Dhiyan Septa Wihara; Bayu Agus Permadi (University of Merdeka Malang, 2025)
This study investigates the role of the Company Identification Number (NIB) as a mediating factor in the relationship between business legality, access to credit, and the competitiveness of Micro, Small, and Medium-Sized Enterprises (MSMEs). Data were collected through structured questionnaires from 95 MSME owners in the Gayungan District of Surabaya and analyzed using Structural Equation Modeling–Partial Least Squares. The findings show that business legality and access to credit positively influence the likelihood of MSMEs obtaining an NIB. In turn, NIB ownership enhances competitiveness and mediates the effect of legality and credit access on competitive advantage. These results underscore the strategic importance of business formalization in strengthening market position and expanding access to financial services. The study suggests that local governments should simplify the NIB registration process, while financial institutions need to implement more inclusive lending schemes. Strengthening both legal compliance and financial access can foster a supportive environment for sustainable MSME growth and competitiveness.